Low-dose lipopolysaccharide (LPS) inhibits aggressive and augments depressive behaviours in a chronic mild stress model in mice. Issue 1 (December 2016) - Couch, Yvonne; Trofimov, Alexander; Markova, Natalyia; Nikolenko, Vladimir; Steinbusch, Harry; Chekhonin, Vladimir; Schroeter, Careen; Lesch, Klaus-Peter; Anthony, Daniel; Strekalova, Tatyana
Abstract Background Aggression, hyperactivity, impulsivity, helplessness and anhedonia are all signs of depressive-like disorders in humans and are often reported to be present in animal models of depression induced by stress or by inflammatory challenges. However, chronic mild stress (CMS) and clinically silent inflammation, during the recovery period after an infection, for example, are often coincident, but comparison of the behavioural and molecular changes that underpin CMS vs a mild inflammatory challenge and impact of the combined challenge is largely unexplored. Here, we examined whether stress-induced behavioural and molecular responses are analogous to lipopolysaccharide (LPS)-induced behavioural and molecular effects and whether their combination is adaptive or maladaptive. Methods Changes in measures of hedonic sensitivity, helplessness, aggression, impulsivity and CNS and systemic cytokine and 5-HT-system-related gene expression were investigated in C57BL/6J male mice exposed to chronic stress alone, low-dose LPS alone or a combination of LPS and stress. Results When combined with a low dose of LPS, chronic stress resulted in an enhanced depressive-like phenotype but significantly reduced manifestations of aggression and hyperactivity. At the molecular level, LPS was a strong inducer of TNFα, IL-1β and region-specific 5-HT2A mRNA expression in the brain. There was also increased serum corticosterone as well as increased TNFα expression in the liver. Stress did not induce comparable levels of cytokine expression to an LPS challenge, but the combination of stress with LPS reduced the stress-induced changes in 5-HT genes and the LPS-induced elevated IL-1β levels. Conclusions It is evident that when administered independently, both stress and LPS challenges induced distinct molecular and behavioural changes. However, at a time when LPS alone does not induce any overt behavioural changes per se, the combination with stress exacerbates depressive and inhibits aggressive behaviours.